IDENTIFYING STUDENTS’ MISCONCEPTION ABOUT INTERMOLECULAR FORCES TOPIC IN ORGANIC CHEMISTRY I COURSE - Widarti, Hayuni Retno; Marfuaf, Siti; Retnosari, Rini (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Intermolecular force is the topic in Organic Chemistry 1 course. Organic Chemistry 1 subject mainly involves abstractive and complex concepts. Therefore, many students face difficulties even get a misconception. This research aimed to identify the students' understanding and misconception in Organic Chemistry 1 lecturing especially about intermolecular forces topic. The study was a quantitative descriptive research. The research subjects were 50 fourth semester Chemistry Education students of 2015-2016 of State University of Malang that have taken Organic Chemistry 1 course. The research instruments were three-tier test namely multiple choices test with open reason and Certainty of Response Index of six items. The conclusion of research result is that 30% of the students still underwent misconception in Organic Chemistry 1 lecturing especially for intermolecular forces topic. The finding of some misconceptions encountered by the chemistry students were the strength of van der Waals forces of more electromagnetive element is more easily polarized; there is no electron withdrawing group in the organic molecules that have dipole-dipole forces so that there are no δ+ and δ-; there is a hydrogen bond in CH3(CH2)2CHO compound; the students did not understand the compound which can form hydrogen and water bond; the hydrogen bond is formed in polar compound; the bond between O-H in CH3(CH2)2COOH molecules is a hydrogen bond; and the strength of intermolecular forces of certain organic molecule is only influenced by electronegativity where the higher the electronegativity the greater the intermolecular forces.